Opportunities and Challenges in the Delivery of mRNA-Based Vaccines - Abishek Wadhwa; Anas Aljabbari; Abhijeet Lokras; Camilla Foged; Aneesh Thakur (MDPI AG, 2020)
In the past few years, there has been increasing focus on the use of messenger RNA (mRNA) as a new therapeutic modality. Current clinical efforts encompassing mRNA-based drugs are directed toward infectious disease vaccines, cancer immunotherapies, therapeutic protein replacement therapies, and treatment of genetic diseases. However, challenges that impede the successful translation of these molecules into drugs are that (i) mRNA is a very large molecule, (ii) it is intrinsically unstable and prone to degradation by nucleases, and (iii) it activates the immune system. Although some of these challenges have been partially solved by means of chemical modification of the mRNA, intracellular delivery of mRNA still represents a major hurdle. The clinical translation of mRNA-based therapeutics requires delivery technologies that can ensure stabilization of mRNA under physiological conditions. Here, we (i) review opportunities and challenges in the delivery of mRNA-based therapeutics with a focus on non-viral delivery systems, (ii) present the clinical status of mRNA vaccines, and (iii) highlight perspectives on the future of this promising new type of medicine.